Formulation, Optimization, and In Vitro–In Vivo Characterization of Furosemide-loaded Poly Lactic-co-glycolic Acid Nanoparticles for Sustained Delivery (Asian Journal of Pharmaceutics (AJP), 2018)
Objective: In this study, the authors developed furosemide-loaded poly lactic-co-glycolic acid (PLGA) nanoparticles (NPs) for sustained delivery of furosemide. Materials and Methods: Furosemide-loaded PLGA-NPs were prepared by emulsion solvent evaporation method and characterized for particle size and size distribution, zeta potential, surface morphology, drug encapsulation efficiency, and drug release profile. In vivo study was performed in Charles Foster rats. Results: In vitro characterizations of the furosemide-loaded PLGA NPs showed that the mean particle sizes of the NPs ranged from 98.3 nm to 300.3 nm, the zeta potential values were in the range of −13.0–−27.1 mV, the encapsulation efficiencies were between 61.0 and 73.4%, and the drug release from the formulation was in the range of 40.3–80.7%. Scanning electron micrographs showed that the fabricated particles were spherical in shape. Urine output at the predetermined time showed a sustained effect of drug in PLGA NPs. Conclusion: The fabricated furosemide-loaded PLGA NPs were able to improve the sustained effect of the drug as indicated in in vitro–in vivo results.